Fertility-sparing treatment for endometrial cancer and atypical endometrial hyperplasia in patients with Lynch Syndrome: Molecular diagnosis after immunohistochemistry of MMR proteins - Catena, Ursula; Della Corte, Luigi; Raffone, Antonio; Travaglino, Antonio; Lucci Cordisco, Emanuela; Teodorico, Elena; Masciullo, Valeria; Bifulco, Giuseppe; Di Spiezio Sardo, Attilio; Scambia, Giovanni; Fanfani, Francesco (Frontiers in Medicine, 2022)
Introduction Lynch Syndrome (LS) represents the hereditary condition that is most frequently associated with endometrial cancer (EC). The aim of this study is to assess the presence of Lynch Syndrome (LS) in young women with mismatch repair (MMR)-deficient atypical endometrial hyperplasia (AEH) and non-myoinvasive FIGO G1 endometrioid EC and its possible impact on the outcome of conservative treatment. Methods Six MMR-deficient cases identified from a previous cohort of 69 conservatively treated patients were selected to be screened for germline mutations in MMR genes. In each patient, the outcomes of conservative treatment for AEH and EEC, including response, relapse, progression, and pregnancy, were assessed. Results Five out of 6 patients underwent genetic test for LS. Three out of these 5 patients showed a positive genetic test. Patient 1 showed the c.942 + 2 T>A heterozygous variant of MSH2 mutation; after 12 months of complete response, she had relapse and progression of disease. Patient 4 showed the c.2459-1G>C variant of MSH2 mutation; after complete response, she failed to achieve pregnancy; she had relapse after 24 months and underwent hysterectomy. Patient 6 showed the c.803 + 1 heterozygous variant of PMS2 mutation; she had relapse of disease after 18 months from the first complete response and then underwent hysterectomy. Conclusions In this series, 3 out of 6 women with MMR-deficiency had LS. None of the patients achieved pregnancy, and those who responded to treatment had subsequent relapse of disease. Patients undergoing fertility-sparing treatment for atypical endometrial hyperplasia and endometrial cancer should perform MMR immunohistochemical analysis in order to screen LS.